2019
DOI: 10.1136/bmjopen-2019-031448
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the clinical ‘Psoriasis in Adolescents’ (PIA) cohort in Denmark

Abstract: PurposePsoriasis is a chronic inflammatory skin disease that frequently debuts in childhood and adolescence. We wished to determine environmental and genetic risk factors for the development of psoriasis in children and adolescents, as well as to investigate debut type, trigger factors, course of disease, nature and influence of stress related to both child and family and risk factors for comorbidity. The ‘Psoriasis in Adolescents’ (PIA) cohort will provide data on the relationship between psoriasis and, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“… IQR, interquartile range; PASI, Psoriasis Area Severity Index, range 0–72; saSPI‐s, self‐assessed Simplified Psoriasis Index (severity subscale), range 0–50; CAM, complementary and alternative medicine. a Concept elicitation interviews (phase 1; n = 18); b cognitive interviews (phase 3; n = 12); c initial validation (phase 4; n = 50); d test–retest sample (phase 5; n = 23); e see the article by Blegvad et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… IQR, interquartile range; PASI, Psoriasis Area Severity Index, range 0–72; saSPI‐s, self‐assessed Simplified Psoriasis Index (severity subscale), range 0–50; CAM, complementary and alternative medicine. a Concept elicitation interviews (phase 1; n = 18); b cognitive interviews (phase 3; n = 12); c initial validation (phase 4; n = 50); d test–retest sample (phase 5; n = 23); e see the article by Blegvad et al …”
Section: Methodsmentioning
confidence: 99%
“…Eligible participants were patients who were aged 12–17 years, had been diagnosed with psoriasis and were able to understand and read Danish. In order for the study to achieve maximum variation in participant demographic and clinical characteristics, participants were recruited from several sites and sources, including two dermatology hospital clinics, the Danish Psoriasis Association (via the summer school, e‐mails to members, and social media), and the Psoriasis in Adolescents cohort . Recruitment sources and demographic details of each sample of patients in the study are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In a smaller clinical subsample of the DNBC – the Psoriasis in Adolescents (PIA) cohort 6 – we were able to investigate tonsillar and perineal carriage of various streptococci. The PIA cohort is a clinical case–control population nested in the DNBC and consisting of 315 adolescents (see Blegvad et al .…”
Section: Cases Controls P‐valuea Gd Not Gdmentioning
confidence: 99%
“…In a study from the Danish National Birth Cohort (DNBC), we found that tonsillitis, especially streptococcal and recurrent tonsillitis, may play a role in paediatric psoriasis. 5 In a smaller clinical subsample of the DNBCthe Psoriasis in Adolescents (PIA) cohort 6 we were able to investigate tonsillar and perineal carriage of various streptococci. The PIA cohort is a clinical case-control population nested in the DNBC and consisting of 315 adolescents (see Blegvad et al for further information).…”
mentioning
confidence: 99%
“…Patients with psoriasis have been reported to have a higher frequency of having autoimmune diseases than healthy controls [ 108 , 109 ]. In a Danish population, children and adolescents with psoriasis showed increased risks of having autoimmune disorders, including rheumatoid arthritis (OR: 6.61; 95% CI: 2.75–15.87) and vitiligo (OR: 4.76; 95% CI: 1.71–13.20), than healthy controls [ 110 ]. Table 5 summarizes the recently reported studies identifying the risk of autoimmune disorders in patients with psoriasis and PsA.…”
Section: The Risk Of Autoimmune Diseases In Psoriasis and Psoriatimentioning
confidence: 99%